2017
DOI: 10.1007/s40865-017-0068-3
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Nature of the Victim-Offender Overlap

Abstract: PurposeIt is well-established that victims and offenders are often the same people, a phenomenon known as the victim-offender overlap, but the developmental nature of this overlap remains uncertain. In this study, we drew from a developmental theoretical framework to test effects of genetics, individual characteristics, and routine-activity-based risks. Drawing from developmental literature, we additionally tested the effect of an accumulation of adverse childhood experiences (ACEs).MethodsData came from the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 113 publications
2
57
1
Order By: Relevance
“…After controlling for genetic and shared environmental confounders (i.e., single-parent household and parental incarceration) in the sibling-comparison models, as well as observed child-specific characteristics (i.e., birth order, maternal age at birth, and sex) to better isolate the environmental influence of ACEs, all direct associations were no longer statistically significant. Accordingly, generated findings from the current study indicate that while traditional between-family analyses report that ACEs are linked to antisocial behavior and victimization, the direct effect of ACEs on these outcomes may be overestimated due to familial factors (Beckley et al, 2018; Connolly & Kavish, 2018). Some readers may reasonably question how this could be the case, given that a wealth of research has reported statistically significant associations between child maltreatment, antisocial behavior, and future victimization.…”
Section: Discussioncontrasting
confidence: 52%
“…After controlling for genetic and shared environmental confounders (i.e., single-parent household and parental incarceration) in the sibling-comparison models, as well as observed child-specific characteristics (i.e., birth order, maternal age at birth, and sex) to better isolate the environmental influence of ACEs, all direct associations were no longer statistically significant. Accordingly, generated findings from the current study indicate that while traditional between-family analyses report that ACEs are linked to antisocial behavior and victimization, the direct effect of ACEs on these outcomes may be overestimated due to familial factors (Beckley et al, 2018; Connolly & Kavish, 2018). Some readers may reasonably question how this could be the case, given that a wealth of research has reported statistically significant associations between child maltreatment, antisocial behavior, and future victimization.…”
Section: Discussioncontrasting
confidence: 52%
“…Apart from focusing exclusively on victims or offenders, substantial evidence exists to suggest a third category of participant in these types of behaviors—that of “victim-offenders” or individuals who have experience as both targets and aggressors (Beckley et al, 2018; Jennings, Piquero, & Reingle, 2012; Posick, 2013). This overlap has been found for bullying (Haynie et al, 2001; Salmivalli & Nieminen, 2002; Veenstra et al, 2005), sexual abuse (Hanson & Morton-Bourgon, 2005; Jennings & Meade, 2016; Veneziano, Veneziano, & LeGrand, 2000), cyberbullying (Hinduja & Patchin, 2015; Marcum, Higgins, Freiburger, & Ricketts, 2014; Mishna, Khoury-Kassabri, Gadalla, & Daciuk, 2012), and dating violence (Espelage & Holt, 2007; Yahner, Dank, Zweig, & Lachman, 2015).…”
Section: Defining and Understanding Sextortionmentioning
confidence: 99%
“…17,18 Second, twin and family studies have reported that psychiatric disorders, violent crime, and subjection to violence tend to aggregate in families, but their etiological associations remain poorly understood. 5,19,20 The literature suggests, however, that the estimates in the studies examining associations between psychiatric disorders and subjection to violence may have been biased upwards because of substantial unmeasured familial confounding.…”
mentioning
confidence: 99%